IMAGE ARTIFACTS AND NO-REFERENCE FEATURE EXTRACTIONS: A REVIEW - Kusuma, Tubagus Maulana (Majalah Ilmiah Matematika Komputer, 2007)
Image attributes, such as shape, orientation, size, texture, gradient, luminance, brightness, andcontrast can be easily recognized by human visual system. All these attributes contribute to thecharacteristics of an image or image features, which reveal uniqueness of the image. Once theimages get corrupted due to compression or transmission, the unexpected artificial features, whichare not existing in the origi